반응형
integral_br_51

51. sec6xdx\int \sec^6x dx

sec6xdx=sec2xsec4xdx(D(tanx)sec2x)=sec4xtanx4sec3xsecxtanxtanxdx=sec4xtanx4sec4xtan2xdx=sec4xtanx4sec4xsec2xsec4xdx=sec4xtanx4sec6xdx+4sec4xdx5sec6xdx=sec4xtanx+4sec4dxsec4dx=sec2x(1+tan2x)dx=sec2xdx+sec2xtan2xdx=tanx+sec2xtan2xdxsec2xtan2xdx(u=tanx,du=sec2xdx)=u2du=13u3=13tan3x5sec6xdx=sec4xtanx+4sec4dx=sec4xtanx+4(tanx+13tan3x)sec6xdx=15sec4xtanx+45tanx+415tan3x+C=15(1+2tan2x+tan4x)tanx+45tanx+415tan3x+C=15tan5x+55tanx+1015tan3x+C=15tan5x+23tan3x+tanx+C \begin{aligned} &\int \sec^6x dx =\int \sec^2x sec^4 x dx\\ &(D( tanx ) \rightarrow sec^2x) \\ &=sec^4x tanx-\int 4sec^3xsecxtanxtanxdx\\ &=sec^4xtanx-4\int sec^4xtan^2x dx\\ &=sec^4xtanx-4\int sec^4xsec^2x-sec^4x dx\\ &=sec^4xtanx-4\int sec^6x dx+4\int sec^4x dx\\ &5\int sec^6x dx = sec^4xtanx+4\int sec^4 dx\\ &\int sec^4 dx=\int \sec^2x (1+\tan^2x) dx=\int sec^2x dx+\int sec^2xtan^2xdx\\ &=\tan{x}+\int sec^2xtan^2x dx\\ &\int sec^2xtan^2x dx (u=tan x, du= sec^2x dx)\\ &=\int u^2 du = \frac{1}{3}u^3=\frac{1}{3}\tan^3{x}\\ &5\int sec^6x dx = sec^4xtanx+4\int sec^4 dx\\ &=sec^4xtanx+4(tan x+\frac{1}{3}\tan^3{x})\\ &\therefore \int sec^6x dx=\frac{1}{5}sec^4xtanx +\frac{4}{5}tanx+\frac{4}{15}tan^3x +C\\ &=\frac{1}{5}(1+2tan^2x+tan^4x)tanx +\frac{4}{5}tanx+\frac{4}{15}tan^3x +C\\ &=\frac{1}{5}tan^5x+\frac{5}{5}tanx+\frac{10}{15}tan^3x +C\\ &=\frac{1}{5}tan^5x+\frac{2}{3}tan^3x+tan {x} +C\\ \end{aligned}
Alternative

sec6xdx=(sec2x)2sec2xdx=(1+tan2x)2sec2xdx(u=tanx,du=sec2xdx)=(1+u2)2du=u4+2u2+1du=15u5+23u3+u=15tan5x+23tan3x+tanx+C \begin{aligned} &\int \sec^6x dx =\int (\sec^2x)^2 sec^2 x dx=\int (1+\tan^2x)^2 sec^2 x dx\\ &(u=tanx, du=sec^2x dx)\\ &=\int (1+u^2)^2 du = \int u^4+2u^2+1du=\frac{1}{5}u^5+\frac{2}{3}u^3+u\\ &=\frac{1}{5}tan^5x+\frac{2}{3}tan^3x+tan {x} +C\\ \end{aligned}


52. 1/(5x2)4dx\int 1/(5x - 2)^4 dx

1(5x2)4dx(u=5x2,du=5dx)=15u4du=115u3=115(5x2)3+C \begin{aligned} &\int \frac{1}{(5x - 2)^4}dx (u=5x-2, du=5dx)\\ &=\frac{1}{5}\int u^{-4}du=-\frac{1}{15}u^{-3}=-\frac{1}{15}(5x-2)^{-3}+C \end{aligned}


53. ln(1+x2)dx\int ln (1+x^2) dx

ln(1+x2)dx=1ln(1+x2)dx=(ln1+x2)(x)2x21+x2dx=xln1+x22x2+111+x2dx=xln1+x22111+x2dx=xln1+x22x+211+x2dx=xln1+x22x+2arctanx+C \begin{aligned} &\int ln (1+x^2)dx =\int 1*ln (1+x^2)dx \\ &=(ln|1+x^2|)(x)-\int \frac{2x^2}{1+x^2} dx\\ &=xln|1+x^2|-2\int \frac{x^2+1-1}{1+x^2} dx\\ &=xln|1+x^2|-2\int 1-\frac{1}{1+x^2} dx\\ &=xln|1+x^2|-2x+2\int\frac{1}{1+x^2} dx\\ &=xln|1+x^2|-2x+2 \arctan{x}+C\\ \end{aligned}


54. 1x4+xdx\int \frac{1}{x^4+x} dx

1x4+xdx=1x(x3+1)dx=1x(x+1)(x2x+1)dx=1x+13x+1+23x+13x2x+1dx=lnx13lnx+123x12(x12)2+34dx=lnx13lnx+113lnx2x+1+C=13lnx313lnx+113lnx2x+1+C=13lnx31(x+1)1(x2x+1)+C=13lnx3x3+1+C=13lnx3+1x3+C=13ln1+x3+C \begin{aligned} &\int \frac{1}{x^4+x} dx =\int \frac{1}{x(x^3+1)}dx \\ &=\int \frac{1}{x(x+1)(x^2-x+1)}dx \\ &=\int \frac{1}{x}+\frac{-\frac{1}{3}}{x+1}+\frac{-\frac{2}{3}x+\frac{1}{3}}{x^2-x+1}dx \\ &=ln|x|-\frac{1}{3}ln|x+1|-\frac{2}{3} \int \frac{x-\frac{1}{2}}{(x-\frac{1}{2})^2+\frac{3}{4}}dx\\ &=ln|x|-\frac{1}{3}ln|x+1|-\frac{1}{3} ln |x^2-x+1|+C\\ &=\frac{1}{3}ln|x^3|-\frac{1}{3}ln|x+1|-\frac{1}{3} ln |x^2-x+1|+C\\ &=\frac{1}{3}ln|x^3\frac{1}{(x+1)}\frac{1}{(x^2-x+1)}+C\\ &=\frac{1}{3}ln|\frac{x^3}{x^3+1}|+C=-\frac{1}{3}ln|\frac{x^3+1}{x^3}|+C\\ &=-\frac{1}{3}ln|1+x^{-3}|+C \end{aligned}
Alternative (미분형태가 나오도록… 차수를 1차이나게…)
1x4+xdx=1x4(1+x3)dx=x41+x3dx(u=1+x3,du=3x4dx)=131udx=13lnu=13ln1+x3+C \begin{aligned} &\int \frac{1}{x^4+x} dx =\int \frac{1}{x^4(1+x^{-3})}dx \\ &=\int \frac{x^{-4}}{1+x^{-3}}dx (u=1+x^{-3}, du=-3x^{-4}dx)\\ &=-\frac{1}{3}\int \frac{1}{u}dx=-\frac{1}{3}ln|u|=-\frac{1}{3}ln|1+x^{-3}|+C \end{aligned}


55. 1tanx1+tanxdx\int \frac{1-tan x }{1+tan x} dx

1tanx1+tanxdx=cosxsinxcosx+sinxdx=cos2xsin2x(cosx+sinx)2dxAlt.=lncosx+sinx+C=cos(2x)1+sin(2x)dx(u=1+sin(2x),du=2cos(2x)dx)=121udu=12ln1+sin(2x)+C \begin{aligned} &\int \frac{1-tan x }{1+tan x} dx \\ &=\int \frac{cos x-sin x }{cos x+sin x} dx =\int \frac{cos^2 x-sin^2 x }{(cos x+sin x)^2} dx \\ Alt. &= ln|cosx+sinx|+C\\ &=\int \frac{cos (2x) }{1+sin(2x)} dx (u=1+sin(2x), du = 2cos(2x)dx)\\ &=\frac{1}{2}\int \frac{1}{u}du\\ &=\frac{1}{2}ln|1+sin(2x)|+C \end{aligned}

12ln1+sin(2x)=ln1+2sinxcosx=lncos2x+sin2x+2sinxcosx=lncosx+sinx \frac{1}{2}ln|1+sin(2x)|=ln|\sqrt{1+2sinxcosx}|\\ =ln|\sqrt{cos^2x+sin^2x+2sinxcosx}|\\ =ln|cos x + sin x|


56. xsec(x)tan(x)dx\int x·sec(x)·tan(x) dx

xsecxtanxdxdx(Dsecsecxtanx)=xsecxsecxdx=xsecxlnsecx+tanx+C \begin{aligned} &\int x \sec{x} \tan{x} dx dx (D sec \rightarrow sec x tan x) \\ &=x sec x - \int sec x dx\\ &=x sec x - ln|sec x+tan x | + C\\ \end{aligned}
Check…
D(xsecxlnsecx+tanx)=secx+x(secxtanx)secxtanx+sec2xsecx+tanx=secx+xsecxtanxsecx=xsecxtanx D(x \sec x - ln|\sec x+\tan x | ) \\ = \sec x+x(\sec x \tan x)-\frac{\sec x \tan x + \sec^2 x}{\sec x + \tan x } \\ = \sec x + x \sec x \tan x - \sec x = x \sec x \tan x


57. arcsec(x)dx\int arcsec(x) dx

arcsec(x)dx(y=arcsec(x),x=sec(y),dx=sec(y)tan(y)dy)=ysec(y)tan(y)dy=ysec(y)sec(y)dy=ysec(y)lnsec(y)+tan(y)(R.Tangle=y,a=1,h=x,o=sqrt(x21))=xarcsec(x)lnx+tan(arcsec(x))+C=xarcsec(x)lnx+x21+C \begin{aligned} &\int arcsec(x) dx \\ &( y=arcsec(x), x=sec(y), dx=sec(y)tan(y)dy )\\ &=\int y sec(y) tan (y) dy = y sec(y) - \int sec(y) dy \\ &=y sec(y) - ln | sec(y)+tan(y) | \\ &(R.T angle=y, a=1, h=x, o=sqrt(x^2-1) )\\ &=x arcsec(x)-ln |x+tan(arcsec(x)) |+C \\ &=x arcsec(x)-ln |x+\sqrt{x^2-1} |+C \\ \end{aligned}
Alt.

D(arcsinx)(y=arcsec(x),x=sec(y),dx=sec(y)tan(y)dy)=dydx=1sec(y)tan(y)=cos2ycscy=(1x)2xx21=1xx21 D(\arcsin{x}) \\ ( y=arcsec(x), x=sec(y), dx=sec(y)tan(y)dy )\\ =\frac{dy}{dx} = \frac{1}{sec(y)tan(y)}=cos^2y \csc y\\ =(\frac{1}{x})^2 \frac{x}{\sqrt{x^2-1}}=\frac{1}{x\sqrt{x^2-1}}

arcsec(x)dx=arcsec(x)(x)1xx21xdx=xarcsec(x)1x21dx \int arcsec(x) dx = arcsec(x)(x)-\int \frac{1}{x \sqrt{x^2-1}} x dx \\ =x arcsec(x)-\int \frac{1}{\sqrt{x^2-1}}dx

1x21dx(x=secθ,dx=secθtanθdθ)=1tanθsecθtanθdθ=secθdθ=lnsecθ+tanθ \int \frac{1}{\sqrt{x^2-1}}dx (x=sec\theta, dx=sec\theta tan\theta d \theta)\\ =\int \frac{1}{tan \theta} sec\theta tan\theta d \theta\\ =\int sec \theta d \theta =ln|sec \theta+tan \theta|

arcsec(x)dx=xarcsec(x)lnsecθ+tanθ(R.Tangle=θ,a=1,h=x,o=sqrt(x21))arcsec(x)dx=xarcsec(x)lnx+x21+C \int arcsec(x) dx =x arcsec(x)-ln | sec \theta+tan\theta| \\ (R.T angle=\theta, a=1, h=x, o=sqrt(x^2-1))\\ \int arcsec(x) dx =x arcsec(x)-ln | x+\sqrt{x^2-1}| +C


58. (1cos(x))/(1+cos(x))dx\int (1 - cos(x))/(1 + cos(x)) dx

1cos(x)1+cos(x)dx=12cos(x)+cos2x1cos2xdx=12cos(x)+cos2xsin2xdx=1sin2xdx2cosxsin2xdx+cos2xsin2xdx \begin{aligned} &\int \frac{1 - cos(x)}{1 + cos(x)}dx \\ &=\int \frac{1-2cos(x)+cos^2x}{1-cos^2x} dx =\int \frac{1-2cos(x)+cos^2x}{sin^2x} dx \\ &=\int \frac{1}{sin^2x}dx-2\int \frac{cos x}{sin^2 x}dx+\int \frac{cos^2x}{sin^2x} dx \end{aligned}

1sin2xdx=cos2x+sin2xsin2x=cos2xsin2xdx+x=cot2xdx+x=csc2x1dx+x=csc2xdx=cotxcosxsin2xdx(u=sinx,du=cosxdx)=duu2=1u=cscxcos2xsin2xdx=cot2xdx=csc2x1dx=cotxx \int \frac{1}{sin^2x} dx=\int \frac{cos^2x + sin^2x}{sin^2x}\\ =\int \frac{cos^2x}{sin^2x} dx +x = \int cot^2x dx +x\\ =\int csc^2x-1 dx+x =\int csc^2x dx = -cot x \\ \int \frac{cos x}{sin^2x} dx (u=sin x, du=cos x dx)\\ =\int \frac{du}{u^2} = -\frac{1}{u}=-csc x\\ \int \frac{cos^2x}{sin^2x} dx =\int cot^2x dx =\int csc^2x-1dx\\ =-cot x - x

=1sin2xdx2cosxsin2xdx+cos2xsin2xdx=cotx+2cscxcotxx=2cscx2cotxx+C=2(cscxcotx)x+C=2(1cosxsinx)x+C =\int \frac{1}{sin^2x}dx-2\int \frac{cos x}{sin^2 x}dx+\int \frac{cos^2x}{sin^2x} dx \\ = -cot x +2 csc x -cot x - x\\ =2 csc x -2cot x -x +C =2 (csc x -cot x) -x +C\\ =2(\frac{1-cos x}{sin x})-x+C\\

=2(1cosx2sinx2)x+C=2(sin2x22sinx2cosx2/2)x+C=2tan(x2)x+C =2(\frac{\frac{1-cosx}{2}}{\frac{sinx}{2}})-x+C\\ =2(\frac{sin^2\frac{x}{2}}{2sin\frac{x}{2}cos\frac{x}{2}/2} )-x+C\\ =2tan(\frac{x}{2})-x+C

Alt.
1cos(x)1+cos(x)dx(sin2(x2)=1cosx2,cos2(x2)=1+cosx2)=sin2(x2)cos2(x2)dx=1cos2(x2)cos2(x2)dx=sec2x2dxx=2tan(x2)x+C \begin{aligned} &\int \frac{1 - cos(x)}{1 + cos(x)}dx \\ &( sin^2(\frac{x}{2})=\frac{1-cosx}{2} , cos^2(\frac{x}{2})=\frac{1+cosx}{2} )\\ &=\int \frac{sin^2(\frac{x}{2})}{cos^2(\frac{x}{2})} dx =\int \frac{1-cos^2(\frac{x}{2})}{cos^2(\frac{x}{2})} dx \\ &=\int sec^2{\frac{x}{2}} dx-x \\ &=2tan(\frac{x}{2})-x+C \end{aligned}


59. (x2)sqrt(x+4)dx\int (x^2)sqrt(x + 4)dx

x2x+4dx(u=x+4,du=12x+4dx)=(u24)2u2udu=2u2(u48u2+16)du=2u616u4+32u2du=27u7165u5+323u3+C=27(x+4)72165(x+4)52+323(x+4)32+C \begin{aligned} &\int x^2\sqrt{x+4}dx \\ &(u=\sqrt{x+4}, du=\frac{1}{2\sqrt{x+4}}dx)\\ &=\int(u^2-4)^2u 2u du=\int 2u^2(u^4-8u^2+16)du\\ &=\int 2u^6-16u^4+32u^2 du\\ &=\frac{2}{7}u^7-\frac{16}{5}u^5+\frac{32}{3}u^3+C\\ &=\frac{2}{7}(x+4)^\frac{7}{2}-\frac{16}{5}(x+4)^\frac{5}{2}+\frac{32}{3}(x+4)^\frac{3}{2}+C\\ \end{aligned}


60. 11sqrt(4x2)dx\int_{-1}^1 sqrt(4 - x^2) dx

114x2dx=2014x2dx(x=2sinθ,dx=2cosθdθ)=20π/62cosθ2cosθdθ=8cos2θdθ=41+cos2θdθ=4θ+2sin2θ=4(π/6)+2(3/2)=2π3+3 \begin{aligned} &\int_{-1}^1 \sqrt{4 - x^2} dx = 2\int_0^1 \sqrt{4 - x^2} dx \\ &( x=2sin\theta, dx=2cos\theta d\theta)\\ &=2\int_0^{\pi/6} 2cos \theta2cos\theta d\theta = 8\int cos^2 \theta d\theta\\ &=4\int 1+cos2\theta d\theta = 4\theta+2sin2\theta \\ &=4(\pi/6)+2(\sqrt{3}/2)\\ &=\frac{2\pi}{3}+\sqrt{3} \end{aligned}


Author: crazyj7@gmail.com

'Math' 카테고리의 다른 글

Integral100 [71-80]  (0) 2019.10.24
Integral100 [61-70]  (0) 2019.10.23
Integral100 [41-50]  (0) 2019.10.21
Integral100 [31-40]  (0) 2019.10.16
Integral100 [21-30]  (1) 2019.10.15

+ Recent posts